Recurrent Right Coronary Artery Occlusion Caused by Cardiac Fibroelastoma Attached to the Aortic Valve. Issue 6 (10th February 2015) - Vimalesvaran, Kavitha; Lumley, Matthew; Child, Nicholas; Redwood, Simon; Blauth, Christopher; Nagal, Eike; Perera, Divaka
Abstract : Supplemental Digital Content is available in the text.